Differential suppressive effects of testosterone on immune function in fresh water snake, Natrix piscator: an in vitro study. - Manish Kumar Tripathi (Public Library of Science (PLoS), 2014)
Reptiles represent the crucial phylogenetic group as they were the ancestors of both birds and mammals hence very important to study. The objectives of the present study were to investigate the potential roles of testosterone in the innate immune responses and splenic lymphocyte proliferation in fresh water snake, Natrix piscator. Animals were mildly anesthetized and spleens were taken out to study the splenic macrophage phagocytosis, super oxide production and nitrite release using in vitro testosterone. Splenic lymphocytes were isolated by density gradient centrifugation and were studied for mitogen induced proliferation in presence of in vitro testosterone. Testosterone suppressed the phagocytosis and nitrite release in a concentration dependent manner. Biphasic suppressive effect of testosterone was observed in superoxide production as judged by reduction of nitroblue tetrazolium salt where salt reduction was suppressed at lower and higher concentrations of testosterone. Mitogen induced splenic lymphocyte proliferation was also suppressed by testosterone. By suppressing immune responses, testosterone may, therefore, act as a physiological mechanism regulating the relative amount of energy invested into either reproductive effort or immunocompetence.